Microbial activity in different soils in response to metribuzin treatment - Šantrić, Ljiljana; Radivojević, Ljiljana; Sarić Krsmanović, Marija; Gajić Umiljendić, Jelena; Đurović-Pejčev, Rada (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2019)
The effect of metribuzin on soil microorganisms and their enzymatic activity, as well as the amount of metribuzin residues, greatly depend on the type of soil and its physico-chemical properties. A laboratory experiment was set up to determine the effects of metribuzin on different groups of microorganisms and dehydrogenase activity in loamy and sandy soils. The amounts of metribuzin residues in those soils were also determined. The following concentrations were tested: 12.0, 24.0; 120.0 and 1200.0 mg a.i. kg-1soil. Samples were collected 3, 7, 14, 30 and 45 days after metribuzin application. Metribuzin acted inhibitively on total bacteria counts in both types of soil: 6.9% in loamy and 7.9% in sandy soils. Actinomycetes counts decreased over the first 14 days after metribuzin treatment by 15.6% in loamy and 8.1% in sandy soil. However, starting with the 30th post-treatment day, their number either increased or remained at the control level. Fungi counts increased by 6.0% seven days after the application of the two highest concentrations. In sandy soil, fungi counts were significantly reduced by 29%. Metribuzin treatment significantly reduced the activity of dehydrogenase enzyme in both types of soil. Only the highest test concentration applied to the sandy soil showed a stimulating effect (33.2 %). Degradation data showed that the measured amounts of metribuzin decreased over time in both types of soil at all four test concentrations. The results showed that the extracted amounts of metribuzin active ingredient at all its test concentrations were greater in the sandy type of soil. Loamy soil was shown to have a better sorption capacity due to its higher contents of organic matter and clay.